Test FOR Dynamic Relationship between Financial Development and Economic Growth in Malaysia: A Vector Error Correction Modeling Approach - Amiruddin, Rosilawati; Mohd Nor, Abu Hassan Shaari; Ismail, Ismadi (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
This paper purports to study the effectiveness of financial development to Malaysian economic growth utilizing quarterly data. In view of the priority given to dynamic relationship in conducting this study, Vector Autoregressive (VAR) method which encompasses Johansen-Juseliusâ Multivariate cointegration, Vector Error Correction Model (VECM), Impulse Response Function (IRF), and Variance Decomposition (VDC) are used as empirical evidence. The result reveals a short-term and long-term dynamic relationship between financial development and economic growth. The importance of financial sector in influencing the economic activity is proven as a clear policy implication.